Media exposure predicts acute stress and probable acute stress disorder during the early COVID-19 outbreak in China - Luo, Yu; He, Xiangcai; Wang, Shaofeng; Li, Jinjin; Zhang, Yu (PeerJ, 2021)
Background The COVID-19 has led to unprecedented psychological stress on the general public. However, the associations between media exposure to COVID-19 and acute stress responses have not been explored during the early COVID-19 outbreak in China. Methods An online survey was conducted to investigate the relationships between media exposure to COVID-19 and acute stress responses, and to recognize associated predictors of acute stress responses on a sample of 1,450 Chinese citizens from February 3 to February 10, 2020. Media exposure questionnaire related to COVID-19 was developed to assess media exposure time, media exposure forms and media exposure content. The Stanford Acute Stress Reaction Questionnaire (SASRQ) was used to measure acute stress responses, including continuous acute stress symptom scores and the risk of probable acute stress disorder (ASD). A series of regression analyses were conducted. Results Longer media exposure time and social media use were associated with higher acute stress and probable ASD. Viewing the situation of infected patients was associated with higher acute stress, whereas viewing the latest news about pandemic data was associated with lower odds of probable ASD. Being females, living in Hubei Province, someone close to them diagnosed with COVID-19, history of mental illness, recent adverse life events and previous collective trauma exposure were risk factors for acute stress responses. Conclusions These findings confirmed the associations between indirect media exposure to pandemic events and acute stress responses. The governments should be aware of the negative impacts of disaster-related media exposure and implement appropriate interventions to promote psychological well-being following pandemic events.
Keywords: COVID-19; Media exposure; Acute stress; Acute stress disorder; Mental health